Water service provision in rapidly urbanising villages: a comparison of rural and urban governance in Mumbai and Chennai regions in India - Haridasan, Renjitha M.; Parker, Alison; Sule, May N. (Royal Society of Chemistry (RSC), 2026)
As cities grow, adjoining villages also start urbanising, adversely affecting primary services, including drinking water services. Switching to urban governance is posed as a solution for addressing this problem. We compared various dimensions of water services available to households across towns in different stages of transition in two metropolitan regions in India to generate evidence on whether the transition of fast-urbanising villages to municipal governance results in improved water services. The data on dimensions of water services were collected through household surveys. The Kruskal–Wallis test was adopted to determine if the differences found in quantitative dimensions of water services available to households across fast-urbanising villages and towns under urban administration were statistically significant, while a chi-square test was employed for qualitative dimensions. Our results showed no better services in towns under urban administration for all dimensions studied. If some were better in towns under urban administration, others were better in urbanising villages under rural administration. We conclude that urban governance alone does not guarantee better services, and there are factors beyond governance contributing to improved services. The findings urge policymakers and programme implementers to look beyond the ‘transition-to-urban governance’ solution and work on institutional strengthening and context-specific approaches. Water impact: Mere transition of fast-urbanising peri-urban areas to urban governance does not, in itself, resolve drinking water challenges in these transition zones. Strengthening the capacities of local governments is essential, irrespective of whether such areas fall under urban or rural administrative arrangements. Policymakers and programme implementers must therefore ensure meaningful involvement of these local governments in urban development planning and adopt inclusive, stakeholder-driven approaches when considering shifts in governance structures.
Keywords: 4407 Policy and Administration; 44 Human Society